Poor state of irrigation statistics in India: the case of wells and tube wells. - Rawat, S.; Mukherji, Aditi (International Water Management Institute, 2012)
This highlight compares data on wells and tube wells, diesel and electric pumps from four sources, namely, Minor Irrigation Census (MIC), Agricultural Census (Ag), Input Survey (InS) and statistics from State Electricity Boards (SEBs) and/ or the State Statistical Bureaus for four time periods representing mid-1980s, 1990s, early 2000s and mid-2000s. Find that more often than not, there is a wide divergence in data - divergence that does not seem to be attributable to mere time lags and definitional differences. This is a cause for serious concern and calls for immediate action and coordination among different government data collection agencies. This is also symptomatic of the overall poor and deteriorating condition of irrigation and other databases in India.